PELATIHAN PENGEMBANGAN PROFESI GURU DALAM BIDANG PENELITIAN DAN PUBLIKASI KARYA ILMIAH DI SEKOLAH DASAR - Rahmi Hayati; Rahmi Wahyuni; Eli Nofriati; Mailiyana; Zuraini Zuraini (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Teachers are the backbone of the country's education system. A professional teacher must have the competence and quality standards as stated in Law 14 of 2005 concerning teachers and lecturers. Teachers and lecturers must be professional in carrying out their work to build quality education through research and community service. The fact is that there are teachers who still experiencing difficulties in carrying out professional development, including research and publication of scientific papers. To help teachers who have difficulty writing scientific work, a community service program was initiated in the form of tutoring and assistance in making scientific work at SD Negeri 5 Juli, Bireuen Regency. The only teacher professional development training that will produce scientific papers and will be presented is Classroom Action Research. Published scientific writing will increase the teacher's confidence in writing and work and make teacher teaching more effective and enjoyable. Everything can be presented in the form of models, making it easier for students to understand the material and get better learning outcomes.